Peer educators' utilisation of information on recognition and referral to refer their peers appropriately - Mphunga, Andile Elvis (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2007.